The Messiah Will Always Come - Klibanoff, Lea (Israel, 2009)
The documentary follows Hagit Ofran, the director of Peace Now’s Settlement Watch team, as she travels across the West Bank in a bid to monitor new settlements. However, the journey also confronts the formerly religious Ofran with her own skepiticism about of Israel’s contemporary religious community.
Verzio Film Festival Submission
Duration: 00:53:00
Verzio Film Festival Submission
Keywords: Documentary films